Molecular Profiling of Sinonasal Adenoid Cystic Carcinoma - Skálová, Alena; Bradová, Martina; Agaimy, Abbas; Laco, Jan; Badual, Cécile; Ihrler, Stephan; Damjanov, Ivan; Rupp, Niels J.; Bacchi, Carlos E.; Mueller, Sarina; Ventelä, Sami; Zhang, Da; et al. (Ovid Technologies (Wolters Kluwer Health), 2025)
Adenoid cystic carcinomas (AdCC) of salivary gland origin have long been categorized as fusion-defined carcinomas owing to the almost universal presence of the gene fusion MYB::NFIB, or less commonly MYBL1::NFIB. Sinonasal AdCC is an aggressive salivary gland malignancy with no effective systemic therapy. Therefore, it is urgent to search for potentially targetable genetic alterations associated with AdCC. We have searched the authors' registries and selected all AdCCs arising in the sinonasal tract. The tumors were examined histologically, immunohistochemically, by next generation sequencing (NGS) and/or fluorescence in situ hybridization (FISH) looking for MYB/MYBL1 and/or NFIB gene fusions or any novel gene fusions and/or mutations. In addition, all tumors were tested for HPV by genotyping using (q)PCR. Our cohort comprised 88 cases of sinonasal AdCC, predominantly characterized by canonical MYB::NFIB (49 cases) and MYBL1::NFIB (9 cases) fusions. In addition, noncanonical fusions EWSR1::MYB; ACTB::MYB; ESRRG::DNM3, and ACTN4::MYB were identified by NGS, each of them in 1 case. Among nine fusion-negative AdCCs, FISH detected rearrangements in MYB (7 cases), NFIB (1 case), and EWSR1 (1 case). Six AdCCs lacked fusions or gene rearrangements, while 11 cases were unanalyzable. Mutational analysis was performed by NGS in 31/88 (35%) AdCCs. Mutations in genes with established roles in oncogenesis were identified in 21/31 tumors (68%), including BCOR (4/21; 19%), NOTCH1 (3/21; 14%), EP300 (3/21; 14%), SMARCA4 (2/21; 9%), RUNX1 (2/21; 9%), KDM6A (2/21; 9%), SPEN (2/21; 9%), and RIT1, MGA, RB1, PHF6, PTEN, CREBBP, DDX41, CHD2, ROS1, TAF1, CCD1, NF1, PALB2, AVCR1B, ARID1A, PPM1D, LZTR1, GEN1, PDGFRA, each in 1 case (1/21; 5%). Additional 24 cases exhibited a spectrum of gene mutations of uncertain pathogenetic significance. No morphologic differences were observed between AdCCs with MYBL1::NFIB and MYB::NFIB fusions. Interestingly, mutations in the NOTCH genes were seen in connection with both canonical and noncanonical fusions, and often associated with high-grade histology or metatypical phenotype, as well as with poorer clinical outcome. Noncanonical fusions were predominantly observed in metatypical AdCCs. These findings emphasize the value of comprehensive molecular profiling in correlating morphologic characteristics, genetic landscape, and clinical behavior in AdCC.